Guides of clinical practice in the management of acute myocardial infarction. Two different periods. - Brandy Viera Valdés; Francisco Valladares Carvajal; Marcos D. Iraola Ferrer; Luis Gustavo Del Sol; Pablo. A. Rodríguez (Medisur)
Background: The elaboration of clinical practice guides has each day a greater significance in the medical attention, but we should not forget its efficacy assessment once they have been established. Objectives: To evaluate the application and impact of the clinical practice guides in the final result of the acute myocardial infarction inn-patients, comparing two different periods of its application (1997 and 2001). Methods: A prospective study of a series of cases in its respective years was done. A total of 315 patients were involved, 154 in 1997; and 161 in 2001. The following variables were analyzed: risk factors, symptoms, complementary tests result, medical attention related aspects, as well as the patient evaluation until dismissal. Results: When comparatively analyzed the two series, a significant mortality reduction in the year 2001 was observed: it lowered from 35, 0 % in 1997 to 17, 4 % in the second patients group. In 2001 the risk of dying from an infarction was two times less than in 1997 (relative risk: 2, 02 (1, 35 – 3, 01). Conclusions: Mortality reduction for myocardial infarction in this hospital could be related, in a high percentage, with the adequate use of the clinical practice guides, used nowadays in the management of such affection.